The Copper scroll revisited - Puech, Emile. (Studies on the Texts of the Desert of Judah, 2015)
This book is the English translation of the new edition of the Copper Scroll of Qumran Cave 3 (3Q15). The restoration of the three sheets of copper by the Mécénat of the French Electric Company (EDF) in the 1990s made an improved decipherment possible. The physical restoration of the complete scroll is published in the two large volumes of the French edition accompanied by many photographs and drawings, which the reader will find to be sufficient. Le Rouleau de cuivre de la Grotte 3 de Qumrân (3Q15). Expertise - Restauration - Épigraphie. Volume I - Texte, Volume II - Planches (2006). The English translation of the new edition of the engraved text will favor easier access to the new results for a wider public.